Projection of further expansion of oil palm plantation in Jambi Province - June, Tania; Ma'rufah, Ummu; Faqih, Ahmad; Koesmaryono, Yonny; Ali, Ashehad Aswen; Knohl, Alexander (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2023)
The expansion of oil palm plantations has become of global concern. Jambi province in Indonesia is one of the regions experiencing a rapid shift in land use, and oil palm plantation, settlement, and agriculture has emerged as the primary force behind this shift. This study aims to project scenarios of future land-use change and expansion of oil palm plantation in Jambi Province in 2030, 2060, and 2100. Projections of land-use change scenarios are conducted using the Land Change Modeler (LCM) in which Cellular Automata Markov (CA-Markov) is the model base. The validation of model against historic land-use changes showed an overall kappa value of 0.97. In the no-conservation scenario assuming a continuation of the trends from 1990 to 2011, the forest area is continuing to decrease. . Oil palm would replace forest as dominant land-use cover in Jambi Province in 2100. Driving factors explaining the spatial distribution of oil palm plantation expansion include distance from forest, distance from road, and elevation. Our study shows the importance of government regulations to to slow or stop deforestation especially for forests near plantations.